Burnout e percepção do clima ético entre trabalhadores de enfermagem de unidade de terapia intensiva Covid – 19 e a organização do trabalho. - Dorneles, Ademir Jones Antunes (2022)
Burnout is a chronic occupational disease that mainly affects people who work with people, it can be associated with the ethical climate (EC), which is a constituent of the organizational climate at work and addresses the collective perception of professionals about the meaning and treatment of ethical issues. in an institution. This study aimed to analyze the association between burnout and ethical climate, as well as its relationship with the relationships in the organization of work in intensive care units (ICU) - covid-19 of university hospitals (HU), in the perception of nursing professionals and managers of these units that acted during the pandemic. This is a mixed study carried out in three HU linked to the Empresa Brasileira de Serviços Hospitalares (EBSERH) in Rio Grande do Sul (RS), Brazil. Data production was designed through a cross-sectional study, with 110 nursing professionals, from December 2021 to March 2022, followed by an exploratory-descriptive study, with six managers of these units from May to July 2022 In the research protocol, the quantitative stage consisted of a questionnaire with sociodemographic and occupational variables; the Maslach Burnout Inventury (MBI) version HSS (Human Services Survey) and the Hospital Ethical Climate Survey_Versão Brasileira (HECS-VB), validated for use in Brazil. In the qualitative stage, a semi-structured interview script was used as an instrument to extract the results of the interviews carried out with the managers of the HU covid-19 ICU. The questions used were designed according to the significant statistical associations (p<0.05) found in the variables in the quantitative stage. Descriptive and analytical statistics were used in the quantitative stage and discursive textual analysis for the qualitative part. When mixing quantitative and qualitative data, they were triangulated to determine explanations and convergences. The ethical aspects of the research were respected according to Resolutions 466/12 and 510/16, obtaining a favorable opinion from the Research Ethics Committee, with the approval record: 5,051,793 and CAAE: 30950420.9.0000. The results showed a prevalence of burnout in nursing professionals of 10% and, according to the dimensions, 30% had high emotional exhaustion, 36.4% high depersonalization and 24.5% low professional fulfillment. Among the participants, 24.5% perceived the ethical climate as negative, highlighting professional exhaustion and emotional and physical changes among the main relations of work organization in these units. Burnout was associated with the perception of the ethical climate by nursing workers, identifying that those in the burnout condition had lower averages for the ethical climate. Those who were in burnout rated the ethical climate as negative in the “doctors” factor. Burnout was associated with the variables: marital status; sons; nursing time at the HU; sector of activity in covid-19; quitting employment and leisure activities. Thus, in relation to burnout and the perception of a negative ethical climate, some physical manifestations, such as exhaustion, fatigue and prostration; emotional, such as: fear, panic, anxiety, distress, nervousness, stress, restlessness and discouragement. The study contributed to research and nursing by identifying the association between burnout and the ethical climate in the scenario of covid-19 in the ICU of covid-19 of the HU; the results may favor UH Directors in the elaboration of educational plans that minimize the deleterious effects of burnout among nursing professionals; as well as promote better working environments, thus impacting on the improvement of health quality.